Peningkatan Hasil Belajar Peserta Didik dalam Pembelajaran Matematika Materi Perbandingan Pecahan Menggunakan Model Pembelajaran Game Based Learning (GBL) di Kelas V SDN 13 Sembilan Koto - Anelta, Raveldio; Ningsih, Yarisda (MASALIQ, 2025)
The problem of low student learning outcomes in mathematics learning in class V SDN 13 Sembilan Koto encourages the need for the use of innovative and fun learning models. This study aims to improve student learning outcomes by applying the Game Based Learning (GBL) model through the development and implementation of mathematics teaching modules. This research is a classroom action research (PTK) conducted in two cycles with qualitative and quantitative approaches. The research subjects were 15 fifth grade students. Data were collected through observation, tests, and non-tests with instruments in the form of observation sheets, test sheets, and rubrics for attitude and skills assessment. The data were analyzed quantitatively using the calculation of the final score and qualitatively through reflective descriptions. The results showed that the teaching module developed increased from 89.25% in cycle I to 96.4% in cycle II. Teacher and learner activities also showed a significant increase, each from the good to very good category. Learners' learning outcomes in the aspects of attitude, knowledge, and skills improved overall, where all learners managed to exceed the Criteria for Completion of Learning Objectives (KKTP). Thus, the use of the Game Based Learning model proved effective in improving the quality of mathematics learning and overall learner learning outcomes.